Lichtheimia ramosa: A Fatal Case of Mucormycosis - Cecilia Mouronte-Roibás; Virginia Leiro-Fernández; Maribel Botana-Rial; Cristina Ramos-Hernández; Guillermo Lago-Preciado; Concepción Fiaño-Valverde; Alberto Fernández-Villar (Canadian Respiratory Journal)
Mucormycosis due to Lichtheimia ramosa is an infrequent opportunistic infection that can potentially be angioinvasive when affecting inmunocompromised hosts. We present a fatal case of mucormycosis, affecting a 56-year-old male with diabetes mellitus and siderosis, initially admitted to our hospital due to an H1N1 infection. The subject’s clinical condition worsened and he finally died because of a necrotizing bilateral pneumonia with disseminated mycotic thromboses due to Lichtheimia ramosa, which is an emerging Mucoralean fungus. This is an infrequent case because of the extent to which it affected a subject without overt immunocompromise. This case underlines the importance of an early premortem diagnosis and treatment in order to prevent rapid progression of this disease, as well as the need of considering mucormycosis when facing subjects with multiple emboli and fever unresponsive to usual antimicrobials.